A review of key national reports to describe the development of paramedic education in England (1966–2014). Issue 12 (7th December 2015) - Brooks, Ingrid Ann; Cooke, Matthew; Spencer, Caroline; Archer, Frank
Abstract : Introduction: In the year 1966, important advances in mobile coronary care and trauma care in the UK and USA influenced globally the development of modern prehospital emergency services and paramedic education. In that year, to meet the evolving role of prehospital care in the UK, the 'Millar Report' specified a new syllabus for ambulance personnel in England. As the 50th anniversary of this report approaches, this paper reviews key national UK reports to describe the development of paramedic education in England over this period. Methods: A hand search of documents available and a Google search identified documents in the public domain. MEDLINE and CINAHL Plus were searched for peer-reviewed publications. Thematic analysis was used to identify descriptive themes. Results: Of the 83 reports and 431 articles screened, 33 documents met our inclusion criteria. We identified four historical periods in English paramedic education: development of paramedic education (1966–1996); paramedic role changes influencing education (1997–2004); paramedic education level changes and the emergency care practitioner (2005–2008); and paramedic education for the future (2010–2014). Our discussion of four descriptive themes: government authority and policy, influence of health professions, quality assurance and development of the paramedic profession includes comparisons with paramedic education in the USA and Australia. Conclusions: Political reform agendas and initiatives and advances in clinical medicine largely shaped paramedic roles and education in England. The degree to which the paramedic profession initiated education development is difficult to determine from the literature. Overall, a nationally coherent standard for paramedic education in England needed five decades to develop and mature.